A Comparative Study between the Blood Pictures of Iraqi Camels Infected with Trypanosomiasis and the Blood Picture of the Healthy Iraqi Camels - Zahra M. Al-Hakak (Journal of Global Pharma Technology, 2018)
This study was conducted to compare the blood picture of healthy Iraqi camels with the blood picture of camels infected with trypanosomiasis. Collected (100) blood samples randomly for a period from 1/10/2015 to 30/9/2016. The blood samples collected from camels which are brought to the veterinary clinic in Najaf and Karbala, from camels that bring to slaughter in the Najaf, Karbala and Qadissiya massacres. These camels some of them healthy and others were observed with illness fatigue, wasting, high Temperature, patches of fall of lint,paleness of mucous membranes and accumulation of edema in different areas of the animal's body. The age of these camels ranged between (8 - 15 years) for camels and she camels. The study included the collection of blood samples and the examination the number of red and white blood cells, count the different type of white blood cells, measure the proportion of hemoglobin and measure pact cell volume of red blood cells .Then make blood smear to see the normal shape of red blood cells and the form of all types of white blood cells to do counting differential type of white blood cells.. We also conduct blood swabs of trypanosomiasis to watch the parasite and make a differential count of white cells and changes in erythrocytes. The results obtained from a sample size (100) camels and she camels, (92) non-infected aninals and (8) animals with trypanosomiasis, the number of healthy camels (60) and (32) animals she camels. The number of infected camels (5) and (3)infected she camels .In healthy camels the number of red blood cells are( 8.6 - 9.9 × 106 / ul),the number of white blood cells are (8.8 - 10.9 × 103 / ul), the percentage of hemoglobin recorded were ( 11.7 - 12.5 g / dl) and the pact cell volume are (48.8 - 48.9%), number of neutrophile( 41.8 -48.9 %) , lymphocytes (35.7 - 42.9%),monocyte (5.7 - 8.4%), eosinophile (3.2 - 4.5%). In all samples we saw one basophile cell in age (8 years - 11 years). In infected animals the number of red blood cells (3.15 - 4.75 × 106 / ul) , white blood cells are (8.9 - 17.5 × 103 / ul), the percentage of hemoglobin recorded in infected animals with trypanosomiasis is (6.5 - 8.5 g / dl)and pact cell volume ( 19 – 24.3 %) .The account of differential type of white blood cells are (36.3 - 50%) neutrophile, lymphocyte (33 - 47.6%), monocyte cells (5-10%), and number of eosinophile (6 - 14)% of the rods did not see any cell.Keywords: Camels, Infected, Iraqi, Comparison, Blood test.